2013
DOI: 10.1371/journal.pone.0080874
|View full text |Cite
|
Sign up to set email alerts
|

Conservation in the Context of Climate Change: Practical Guidelines for Land Protection at Local Scales

Abstract: Climate change will affect the composition of plant and animal communities in many habitats and geographic settings. This presents a dilemma for conservation programs – will the portfolio of protected lands we now have achieve a goal of conserving biodiversity in the future when the ecological communities occurring within them change? Climate change will significantly alter many plant communities, but the geophysical underpinnings of these landscapes, such as landform, elevation, soil, and geological propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In some parts of the world, certain combinations of soils and topography, such as serpentine soils or limestone karst outcrops, are widely recognized for their unique contributions to current biodiversity, but global conservation priorities are not generally based on land facets. This is despite the fact that land facet diversity appears to be strongly correlated with species diversity, and thus may be particularly effective in areas where species distributions are poorly known, particularly aquatic environments . In one application of land facets, Brost and Beier found that corridor linkages determined by land facets provided as much or more connectivity for a suite of focal species as a consensus corridor plan based on the species themselves.…”
Section: Coarse‐filter Approaches: Conserving the Stagementioning
confidence: 99%
“…In some parts of the world, certain combinations of soils and topography, such as serpentine soils or limestone karst outcrops, are widely recognized for their unique contributions to current biodiversity, but global conservation priorities are not generally based on land facets. This is despite the fact that land facet diversity appears to be strongly correlated with species diversity, and thus may be particularly effective in areas where species distributions are poorly known, particularly aquatic environments . In one application of land facets, Brost and Beier found that corridor linkages determined by land facets provided as much or more connectivity for a suite of focal species as a consensus corridor plan based on the species themselves.…”
Section: Coarse‐filter Approaches: Conserving the Stagementioning
confidence: 99%
“…For instance, areas which have high geodiversity have a high conservation value (see e.g. Anderson and Ferree 2010, Beier and Brost 2010, Ruddock et al 2013. Third, species richness and other factors that contribute to conservation values have connections.…”
Section: Synthesizing Resultsmentioning
confidence: 99%
“…In a changing climate, it has been argued that areas with the elements to provide high biodiversity in the future should be targeted (Anderson and Ferree 2010, Beier and Brost 2010, Ruddock et al 2013. The same could also be applied to other constituents of conservation value.…”
Section: Synthesizing Resultsmentioning
confidence: 99%
See 2 more Smart Citations